Failure To Complete Mathematics Homework Among Year 3 Pupils Of SK Jalan Ong Tiang Swee, Kuching / Sharifah Hanifah Maulad Wan Mohamad - Wan Mohamad, Sharifah Hanifah Maulad (2015)
The purpose of this study was to identify factors failure of Year 3 students in math homework and identify strategies that can be used to overcome this problem. This study focused on students in Years 3 in SK Jalan Ong Tiang Swee, Kuching. To find the information needed to complete this study, two instruments were used, namely the survey and interview methods. Twenty-five students were chosen as respondents in this study to identify the factors that have led to the failure of students to complete homework. While to identify strategies that can be used to overcome this problem, two mathematics teachers were interviewed. Results ofstudies have found that there are several factors that have affected the student fail to complete math homework. The factors were first, pupils does not acknowledge that by doing homework it can helped them to learn the subject more effectively, second, the teachers seldom gave them any explanations on how to do the homework and third factor was from the parents who seldom encouraged their children to finish their homework. There are three strategies that have been identified that can help to overcome this problem, namely the number of questions, the level of appropriate questions and implement reward system. Beside that, the guidelines provide homework from the Ministry of Education may also be referred to ensure that it is implemented effectively. In conclusion, this study is expected to help teachers to solve the problem ofstudents unable to complete their homework.